Increasing Adolescent Awareness of the Dangers of Early Marriage through Socialization at SMKN 1 Praya Barat, Central Lombok - Debra Ayu Citra Ningrum; Ratniah Saputri; Nurjana Nurjana; Dini Rohmawati; Mardianti Amriani; Syamsuddin Syamsuddin; Rahmatun Inayah; Ika Umratul Asni Aminy; Adella Ulyandana Jayatri; Kormil Saputra (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2026)
Early marriage remains a serious social issue in Indonesia, particularly in rural areas. This community service activity aimed to raise awareness and improve adolescents’ understanding of the dangers of child marriage through an interactive socialization program at SMKN 1 Praya Barat, Central Lombok Regency. The implementation consisted of three main stages: preparation (developing materials and instruments), execution (educational sessions with visual media, discussions, and Q&A), and evaluation (through pre-test and post-test). The results showed a significant 22.8% increase in students’ understanding, especially regarding legal aspects, reproductive health, and the socio-economic impacts of early marriage. About 71% of students expressed a commitment to delay marriage until completing senior high school, while 82% of female students demonstrated better awareness of reproductive health planning. This activity effectively fostered legal, social, and moral awareness among adolescents and encouraged school and community participation in preventing early marriage practices.